Kedudukan Anak Angkat Dalam Pembagian Warisan Menurut Hukum Islam - Karim, Atoillah (Universitas Wiralodra, 2016)
The children is a gift and also as a mandate to educate and well bred. Because it is importance of the presence of a Child as a successor to the descendants of as a complement to happiness hearts, so those alternatives is endowed children and it is some regulation of govermnet to guidelines Adoption of child. And also to review the legal certainty so get must apply for Adoption to Justice, however in the aplication although adoption of children is legitimate based on regulation, but it has little difference between hearts inheritance distribution process Bladder and Adopted Children.